Bridging the Gap: Leveraging AI to Address Talent Shortages in Organizations - Muhammad ZEESHAN; Umar ALI; Sameer ALI (Journal of Human Resource Management)
Purpose - The purpose of this paper is to provide insights into the effectiveness of AI in optimizing recruitment strategies and overcoming challenges related to talent acquisition. Aim - This study aims to investigate the impact of AI tools, such as predictive analytics, chatbots, and automated screening, on recruitment processes. It seeks to highlight how these technologies can reduce time-to-hire, improve decision-making, and enhance workforce diversity while addressing critical issues such as AI biases and data privacy. Design/Methodology/Approach - The research adopts a literature review methodology, synthesizing findings from existing studies on AI technologies in recruitment. It examines key AI applications, ethical challenges, and best practices for AI-driven talent acquisition. The study also provides recommendations based on a review of evidence-based practices in organizations that have implemented AI in their recruitment processes. Findings - The study finds that AI can significantly improve recruitment efficiency by automating repetitive tasks, streamlining the hiring process, and providing more informed decision-making. However, it also reveals ongoing challenges with AI biases, ethical concerns, and data privacy. These issues necessitate transparency, regular audits, and comprehensive training for HR professionals to ensure the responsible and effective use of AI. Limitations of the Study - The study is limited by its reliance on secondary data from existing literature, which may not fully capture emerging trends or specific organizational contexts. Additionally, the ethical and practical challenges of AI adoption in recruitment require further empirical research to validate the findings across different industries. Originality/Value - This paper highlights both the opportunities and risks associated with AI adoption in recruitment and provides organizations with practical recommendations for navigating ethical and operational challenges while leveraging AI for improved hiring outcomes.